Aplikasi Pengarsipan Surat Untuk Peningkatan Pelayanan Desa Bumi Arum - Imamuddin Imamuddin; Muhamad Muslihudin; Joni Joni (Institut Bakti Nusantara, 2020)
Archives are determinants in the process of implementing agency tasks, especially in government agencies that are oriented towards providing services directly to the public (public). In the world of work and government today technology is the main point in carrying out all work activities using existing resources, namely computers and internet networks. for the system development method in the archive management system in this study is the Waterfall model. Waterfall Model or also called linear sequential model proposes an approach to the development of systematic and sequential software starting at the level and progress of the system in analysis, coding design, testing and maintenance. The implementation of an Android-based filing application can be built and run well on Android for the BumiArum office hall and the BumiArum village community. From a research that the researcher did has produced an Archiving Application in BumiArum Village which helped a little more in processing archives in the BumiArum summit office.